Clinical Outcomes of Scleral Lens Fitting with a Data-driven, Quadrant-specific Design: Multicenter Review. Issue 9 (September 2020) - Barnett, Melissa; Carrasquillo, Karen G.; Schornack, Muriel M.
Abstract : SIGNIFICANCE: Alignment of the scleral lens haptic with the anterior ocular surface is of critical importance when fitting scleral lenses. The concept of leveraging big-data analysis to drive lens design is explored in this study. This retrospective study evaluated fitting outcomes of a data-driven, quadrant-specific scleral lens design and found that most patients (76%) were successfully fit with this design. PURPOSE: The purpose of this study was to evaluate clinical outcomes with a data-driven, quadrant-specific scleral lens design compared with traditional lens designs. METHODS: For this multicenter retrospective observational study, A REDCap (Research Electronic Data Capture) survey was distributed to scleral lens practitioners who participated in β testing of a data-driven, quadrant-specific scleral lens design (study lens) between June 1, 2016, and January 31, 2017. Descriptive data were collected, and patient-reported outcomes, visual acuity, and lens design outcomes achieved with the study lens were described. RESULTS: Seventy-five patients (85 eyes) were fit with the study lens design between June 2016 and January 2017. Mean patient age was 47 years (range, 17 to 77 years). Forty-six were male, and 29 were female. Seventy-six eyes (89%) were fit for corneal irregularity, whereas nine eyes (11%) were fit for management of ocular surface disease. Compared with habitual correction, 22% more eyes achieved 20/20 or better, and 21% more eyes achieved 20/40 or better. There was also a 60% decrease in the need for midday removal with the study lens. An average of two lenses were manufactured per eye to complete the fitting process. CONCLUSIONS: Using a data-driven, quadrant-specific scleral lens resulted in visual improvement, a reduced need for midday removal, and an average of two lenses needed to complete the fitting process. Longer-term clinical outcomes and the use of big-data analysis to inform scleral lens design should be further explored.